Experimental investigation on the performance enhancement of heat transfer characteristics of electronic chip cooling using metal matrix composites. Issue 11 (18th September 2020) - Ramesh, V.; Prakash, Surrya; Venkatasudhahar, M.; Logesh, K.; Dilip Raja, N.; Yogaraj, D.
ABSTRACT: Over the period of years, numerous investigations were made to enhance the heat transfer characteristics of metal matrix composites by various researchers. In these research, eight different groups of Aluminium and silicon carbide (Al & SiC) combinations were used. Each combination group was examined with three-level thermal conductivity materials used for this investigation. Using metal matrix composites, thermal conductive materials of different composition were experimentally investigated for the enhancement of performance of heat transfer characteristics of electronic chip cooling through thermal conduct resistance.